3d Printing Modelling In Malaysian Construction Industry - Wong, Yinn Han; Chan, Siew Chong (2016)
Three-dimensional (3D) printing has long been used in the manufacturing sector as a way to automate, accelerate production and reducing waste materials. By using this technology, it is possible to build a wide variety of objects provided that (i) the necessary specifications are provided to the printer and (ii) no material limitation problems. With 3D printing becoming cheaper, more reliable and, as a result, more prevalent to the world at large, it may soon make inroads into the construction industry. However, little is known about 3D printing usage in the construction industry and its potential for the future. Thus, this paper seeks to investigate this situation by providing a review of the relevant literature. The method chosen for this research was the descriptive survey approach through conducting interviews with targeted interviewees in order to collect their opinions regarding onto development and application of 3D printing in Malaysia. The findings shows that there are some potentials usage of 3D printing in the future, although its application is low in current stage due to high cost and strong contractors preference in traditional methods.